Volumetric Properties of Concrete under True Triaxial Dynamic Compressive Loadings - Cui, J.; Hao, Hong; Shi, Y.; Zhang, Xihong; Huan, S. (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
Almost all of the available test data for pressure-volumetric strain curves [equations of state (EoS)] of concrete are based on static triaxial tests and one-dimensional impact tests, for example, the flyer-plate impact test, because of a lack of equipment for conducting synchronized triaxial impact tests. The EoS based on static triaxial and dynamic uniaxial tests does not necessarily represent the true behavior of concrete under hydrodynamic loadings. Therefore, to derive an accurate dynamic EoS of concrete material, it is essential to develop reliable techniques for conducting true synchronized triaxial impact tests. This paper presents an innovative three-dimensional split-Hopkinson pressure bar (3D-SHPB) test system recently developed by the authors and some preliminary test results. A comparison of true triaxial dynamic test results and true triaxial static test results was carried out. It was found that the bulk modulus of concrete was strain-rate sensitive. Theoretical and numerical analyses with a mesoscale model were carried out to examine and explain the test observations. It was found that the increase in bulk modulus under hydrodynamic loadings could be at least partially attributed to water pressure, because the pore water in the cement paste could be drained during the dynamic loading phase. The resistance of microscopic viscosity to the development of microcracks is another reason for the strain rate sensitivity of the bulk modulus. An empirical relation is proposed in this study for the dynamic increase factor (DIF) of the concrete bulk modulus with respect to the strain rate.